2022
DOI: 10.2147/ceor.s355507
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Primary Health Care Specialized Reference Clinics in Riyadh First Health Cluster: Outcome, Cost-Effectiveness and Patient Satisfaction

Abstract: Purpose The objectives of the study are to assess the outcome and cost-effectiveness of specialized reference clinics (SRCs) in primary health care centers (PHCCs) of Riyadh First Health Cluster (RFHC), then to estimate the patient satisfaction among clients utilizing such SRCs. Patients and Methods This facility-based study was conducted in Riyadh city, Saudi Arabia among six PHCCs in RFHC that contain SRCs. Records of all patients utilizing SRCs and their referral inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…Accessibility of health care, organization of its PISSN: 2974-3281 EISSN: 2974-329x services, treatment length, clinic structure, and competence of physicians are the core factors related to client/patient satisfaction. (28) Physical infrastructure and surroundings can affect a client's/patient's perception about the quality of services received. (22) The current study reveals that more than three quarters of the clients had low level of satisfaction in services' general quality, structure, and process especially for those at Damanhour PHC Centers.…”
Section: Discussionmentioning
confidence: 99%
“…Accessibility of health care, organization of its PISSN: 2974-3281 EISSN: 2974-329x services, treatment length, clinic structure, and competence of physicians are the core factors related to client/patient satisfaction. (28) Physical infrastructure and surroundings can affect a client's/patient's perception about the quality of services received. (22) The current study reveals that more than three quarters of the clients had low level of satisfaction in services' general quality, structure, and process especially for those at Damanhour PHC Centers.…”
Section: Discussionmentioning
confidence: 99%
“…The studies identified on this topic indicated that patients were overall satisfied with PHC services in KSA but saw the need for improvements in some areas. 20,22,27,41,46 Waiting time for appointments is a quality attribute that is regularly employed to measure patient satisfaction with PHC services. Two study reported high levels of patients satisfaction overall but accessibility and waiting time needed to be improved.…”
Section: Patients' Perceptions Of Phc In Ksamentioning
confidence: 99%
“…In terms of the health professionals' perceptions of some aspects of PHC services, several studies examined their perceptions of the use of electronic health records (EHRs), 14,15,23 safety culture, 36,38 communicable disease management, 29 emergency services, 30 laboratory services, 26 and how cost-effective are the specialized reference clinics. 22 Electronic health records (EHR) are vital for the delivery of high-quality health care. [51][52][53] Three studies examined the professionals' perception of EHRs use and their role in improving the quality of PHC services.…”
Section: Patients' Perceptions Of Phc In Ksamentioning
confidence: 99%
See 1 more Smart Citation